Colloids for Nano- and Biotechnology - Hórvölgyi, Zoltán; Kiss, Eva.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This volume contains a selection of the papers presented at the 9th Conference on Colloid Chemistry. A colloid chemical approach to nano- and biotechnology was one of the main topics of the meeting held in Siófok, Hungary in October 2007. It was organized by the Hungarian Chemical Society in cooperation with leading Hungarian universities and the Hungarian Academy of Sciences. The contributions demonstrated the progress of the field and supported that "The world of neglected dimensions" should not be neglected at all in modern material sciences and technologies. This volume is intended for professionals dealing with fundamental research or development of industrial applications, who encounter colloids, nanostructures, and interfacial phenomena during their work.
Colloid Science for Functional Nanomaterials: Application to Oxide Ceramic Membranes -- Biopolymer Gels: Nanostructure and Macroscopic Properties -- Energy Transfer from CdSe/ZnS Nanocrystals to Zinc-Phthalocyanine for Advanced Photon Harvesting in Organic Photovoltaics -- Photocatalytic Degradation of Anionic Surfactant in Titanium Dioxide Suspension -- Magnetite Nanoparticles Stabilized Under Physiological Conditions for Biomedical Application -- Preparation and Characterization of Hexagonal W-type Barium Ferrite Nanoparticles -- Preparation and Characterization of Y-Fe-Al Garnet Nanostructured Materials -- Colloid Characteristics and Emulsifying Properties of OSA Starches -- Preparation and Characterization of Barium Sulfate Particles as Contrast Materials for Surgery -- Aluminium Salts Hydrolysis Products from Industrial Anodising Sludges in Wastewater Treatment -- Strength of Flocs Formed from Aluminium Sulfate Hydrolysis Product Particles -- Nanolayer Coatings -- Amphiphilic Nature of New Antitubercular Drug Candidates and Their Interaction With Lipid Monolayer -- Complexation of Statins with ?-Cyclodextrin in Solutions of Small Molecular Additives and Macromolecular Colloids -- Investigating the Effect of Adding Drug (Lidocaine) to a Drug Delivery System Using Small-Angle X-Ray Scattering -- Zinc Oxide LB Films with Improved Antireflective, Photoactive and Mechanical Properties -- Drug Release and Skin Permeation from Lipid Liquid Crystalline Phases -- Comparative Study of Calcium Silicate Bulk Systems Produced by Different Methods -- Morphological Characterization of Oxidized and Metal Impregnated Spherical Carbons -- The Effect of Ionic Environment on the Adsorption of Phenol -- On the Magnitude of Line Tension -- Autophobic Wetting and Captation -- Adsorption of the SDS on Coal -- Thermally-Induced Effects in Oriented Network of Amyloid ?25–35 fibrils -- Temperature Induced DNA Compaction in a Nonionic Lamellar Phase -- A Two-step Aggregation Scheme of Bile Acid Salts, as Seen From Computer Simulations -- Interaction of Cetyl Trimethylammonium Bromide With Poly-(N-Isopropylacrylamide-Co-Acrylic Acid) Copolymer Nanogel Particles -- Characterization of Poly(N-isopropylacrylamide) and Magnetic Poly(N-isopropylacrylamide) Latexes -- NMR Study of Poly(?-Glutamic Acid) and Partially Benzylated Poly(?-Glutamic Acid): Nanoparticles in Solution -- IASON – Intelligent Activated Sludge Operated by Nanotechnology – Hydrogel Microcarriers in Wastewater Treatment -- Effect of Interactions, Molecular and Phase Structure on the Properties of Polyurethane Elastomers -- Flower Petal-like Pattern on Soft Hydrogels during Vodka Spreading.
Keywords: Polymers .; Nanotechnology; Biotechnology; Polymer Sciences; Nanotechnology; Biotechnology